Simulation of Urban Drainage System Using a Storm Water Management Model (SWMM) - Rangari, Vinay Ashok; Sai Prashanth, Sriramoju; Umamahesh, N. V.; Patel, Ajey Kumar (Asian Journal of Engineering and Applied Technology, 2018)
Urban floods are caused due to increase in population density, development of urban infrastructure without paying due consideration to drainage aspects and increase in paved surfaces. Storm water modelling plays an important role in checking issues such as flash floods and urban water-quality problems. The SWMM (Storm Water Management Model) has been an effective tool for simulating floods in urban areas. In this study a SWMM model is developed to analyze drainage network for the campus of National Institute of Technology, Warangal in the city of Warangal, Telangana, India. The model is simulated for one real storm event and 2-year return period of interval 1-hour design storm intensity. Frequency analysis is performed using best fitted distribution i.e., Gumbel’s distribution for different return periods and the frequency values are used for development of IDF (intensity-duration-frequency) curves. Design storm intensity derived from IDF curves for different return periods is used to estimate peak runoff from each sub catchment which is used as input parameter in simulation of runoff in SWMM. GIS methodology is employed for handling spatial data simultaneously. From results, it is observed that some part of campus are commonly affected with flooding, when analysis is performed for two design storms and one day continuous rainfall/precipitation values.